Singgasana Keraton Ngayogyakarta Hadiningrat dalam Dialektika Universalisme Vs. Partikularisme HAM: (Komentar terhadap Putusan MK 88/PUU-XIV/2016) - Febriansyah Ramadhan; Luthfi Marfungah (CV Rewang Rencang, 2020)
This article will elaborate on the study of women seen from the lens of universalism vs. human rights particularism in Decree No. 88/PUU-XIV/2016. The ruling is about the gender requirements or the necessity to have a wife in charging the Sultan of Yogyakarta. Allegations of discrimination pinned by the petitioners and judges of the Court of Justice against the condition will be the main focus in this study. The main headline or argument built by the petitioners through his power and also the nine judges of the Constitutional Court is